2003
DOI: 10.1093/jn/133.11.3369
|View full text |Cite
|
Sign up to set email alerts
|

A Licorice Ethanolic Extract with Peroxisome Proliferator-Activated Receptor-γ Ligand-Binding Activity Affects Diabetes in KK-Ay Mice, Abdominal Obesity in Diet-Induced Obese C57BL Mice and Hypertension in Spontaneously Hypertensive Rats

Abstract: The metabolic syndrome, including type 2 diabetes, insulin resistance, obesity/abdominal obesity, hypertension and dyslipidemia, is a major public health problem. Peroxisome proliferator-activated receptor-gamma (PPAR-gamma) ligands such as thiazolidinediones are effective against this syndrome. In this study, we showed that nonaqueous fractions of licorice (Glycyrrhiza uralensis Fisher) extracted with ethanol, ethyl acetate and acetone, but not an aqueous extract, had PPAR-gamma ligand-binding activity with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
67
0
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(75 citation statements)
references
References 48 publications
4
67
0
4
Order By: Relevance
“…9,10) Licorice flavonoid oil (LFO), which contains hydrophobic flavonoids from G. glabra LINNE, is a new ingredient for functional foods. [9][10][11][12] We recently found that LFO decreases the size of hepatic lipid droplets, which are mainly composed of triglyceride (TG), and abdominal adipose tissue weight in diet-induced obese mice. 10) It is well-known that TG is synthesized in the liver, secreted into the blood-stream, and transported to the peripheral organs, including the adipose tissues.…”
Section: Investigation Of the Anti-obesity Action Of Licorice Flavonomentioning
confidence: 99%
“…9,10) Licorice flavonoid oil (LFO), which contains hydrophobic flavonoids from G. glabra LINNE, is a new ingredient for functional foods. [9][10][11][12] We recently found that LFO decreases the size of hepatic lipid droplets, which are mainly composed of triglyceride (TG), and abdominal adipose tissue weight in diet-induced obese mice. 10) It is well-known that TG is synthesized in the liver, secreted into the blood-stream, and transported to the peripheral organs, including the adipose tissues.…”
Section: Investigation Of the Anti-obesity Action Of Licorice Flavonomentioning
confidence: 99%
“…Glycyrrhizic acid, the main active ingredient of licorice root extracts [57][58][59], is a triterpenoid glycosidic saponin used as a sweetener. Glycyrrhizic acid is converted in glycyrrhetinic acid in the small intestine by the activity of the intestinal microbiota and undergoes an extensive metabolic biotransformation in the liver [57][58][59]. Thus, glycyrrhizic acid is not detectable in the blood.…”
Section: Fxr Is a Potential Mediator Of Beneficial Effects Of Licoricmentioning
confidence: 99%
“…Despite their beneficial effects on ulcer healing, extracts of licorice roots are known to produce severe hypertension and hypokalemia [57][58][59]. This mineralcorticoid-like syndrome is primarily caused by the inhibition of 11b-hydroxysteroid dehydrogenase, an enzyme that inactivates intracellular glucocorticoids in mineralocorticoid-responsive organs, such as the kidney, increasing relative levels of cortisol, which stimulates aldosterone receptors, leading to a functional mineralocorticoid excess [57][58][59].…”
Section: Fxr Is a Potential Mediator Of Beneficial Effects Of Licoricmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15] . Glycyrrhiza glabra are reported to be used as sweetners, flavorings and as herbal medicine and also used for improving health, detoxification, antioxidant property and cures for injury [16][17][18][19][20] . Camellia sinensis commonly known as green tea reported to have anticarcinogenic, antiviral, antioxidant property, antibacterial, antigentoxic activity etc [21][22][23][24] .…”
Section: Introductionmentioning
confidence: 99%